2012
DOI: 10.3109/01480545.2012.710623
|View full text |Cite
|
Sign up to set email alerts
|

In vitroinduction/inhibition of germinal vesicle breakdown (GVBD) in frog (Euphlyctis cyanophlyctis) oocytes by endocrine active compounds

Abstract: Oocyte maturation is transformation of oocytes into a fertilizable egg. This study examined the effects of four classes of chemicals: 1) acephate (organophosphate); 2) atrazine (herbicide); 3) cypermethrin and fenvalerate (synthetic pyrethroids); and 4) carbaryl (carbamate) on in vitro germinal vesicle breakdown (GVBD) of Euphlyctis cyanophlyctis oocytes. Follicles were isolated and defolliculated from surgically removed ovaries of E. cyanophlyctis and exposed to either progesterone (1 μM/mL) or graded concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Our results indicate that just as in other models, in our experimental model, atrazine has direct toxic effects on porcine oocytes in vitro [23, 25]. Similar results have been reported in porcine oocytes, namely, that treatment with atrazine decreases oocyte meiotic maturation [36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results indicate that just as in other models, in our experimental model, atrazine has direct toxic effects on porcine oocytes in vitro [23, 25]. Similar results have been reported in porcine oocytes, namely, that treatment with atrazine decreases oocyte meiotic maturation [36].…”
Section: Discussionsupporting
confidence: 87%
“…A few studies have shown toxic effects of atrazine on oocyte quality in vitro in Xenopus frogs and Japanese medaka models [2325]. These studies have revealed that atrazine is detrimental to oocyte maturation; however, the mechanisms of toxicity are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have described effects of EDCs on gonadal differentiation, the secondary sex characteristic development, and metamorphic process of amphibians (Crump et al, 2002;Hayes et al, 2002Hayes et al, , 2010Porter et al, 2011;Qin et al, 2003). Also, some of EDCs, such as ethinyl estradiol, atrazine, 2,4-dichlorophenoxyacetic acid and methoxychlor, have been shown to affect oocyte maturation in amphibians, suggesting potential adverse effects on reproductive function of amphibians (Fort et al, 2002;Ghodageri and Katti, 2013;Pickford and Morris, 1999;Stebbins-Boaz et al, 2004). Given that androgens can induce oocyte maturation and anti-androgen flutamide can inhibit androgen-induced oocyte maturation, we propose that environmental androgens and anti-androgens could disrupt oocyte maturation of amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of the analysis, two papers overlooked during the development of the original WoE assessment were identified and analyzed. In the end, the papers included in the QWoE update are: (Chang et al 2005;Hecker et al 2005;Svartz et al 2012;Ghodageri and Katti 2013;Olker 2014;Shenoy 2014;Baxter et al 2015;Chen et al 2015;Sai et al 2015Sai et al , 2018Syngenta 2015Syngenta , 2017aSyngenta , 2017bVan Der Kraak et al 2015;Wirbisky and Freeman 2015;dos Santos Mendonc¸a et al 2016;Ehrsam et al 2016;Gustafson et al 2016;Khan et al 2016aKhan et al , 2016bKhan et al , 2016cLiu et al 2016;Richter et al 2016;Russart and Rhen 2016;Tulaby Dezfuly and Mohammadian 2016;Wirbisky et al 2016aWirbisky et al , 2016bWirbisky et al , 2016cD'Angelo and Freeman 2017;Du Gas et al 2017;Hoskins et al 2017;Jones et al 2017;Khalil et al 2017;Kirsten et al 2017;McMahon et al 2017;Persch et al 2017;Scott et al 2017;Shukla et al 2017;Snyder et al 2017;Wang et al 2017;…”
Section: Methodsmentioning
confidence: 99%
“…There were three new studies on the effects of atrazine on in vitro cultures of tissue, one for an amphibian and two for fish ( Figure 24). Atrazine at concentrations of 1000 to 20,000 mg/L was reported to induce breakdown of germinal vesicle in the ovarian follicles of the frog (Euphlyctis cyanophlyctis) (Ghodageri and Katti 2013). All these concentrations were not environmentally relevant.…”
Section: Physiological and Biochemical Effects In Vitromentioning
confidence: 99%